A Bibliometric Study on the Top 101 Most-Cited Articles of Dental Journals of the Middle East/North Africa Countries From 2011 to 2021: Top 101 articles in dental journals of Middle East - Roghanizadeh, Leyla; Akbarzadeh Baghban, Alireza; Azizzadeh, Jila; Asgary, Saeed (Journal of Lasers in Medical Sciences, 2023)
Introduction: This retrospective descriptive study evaluated the Scopus-indexed dental journals and their most-cited documents affiliated with the Middle East and North Africa (MENA) countries from 2011 to 2021. Methods: Dental journals affiliated with MENA countries, their bibliometric indicators (SJR, CiteScore, SNIP, and H-index), and the 101 most cited articles of the considered journals were extracted and studied through descriptive statistics. In addition, the “citation per year” of each top 101 articles was calculated. Spearman’s rho test was used for pairwise comparisons of the correlation coefficient values between each two of the considered bibliometric indicators. Results: The number of citations of the 101 most-cited papers ranged from 35 to 203. The mean (SD) citations of studied articles were 61.33 (37.58) and the median was 46. Furthermore, CiteScore had the highest significant correlation with SJR (r=0.828, P˂0.001). Moreover, the citation per year of the top 101 documents had no significant relationship with any of the journals’ bibliometric indicators. Conclusion: Because journal performance and citation rate are multi-dimensional concepts, a single metric cannot express them thoroughly despite correlations between indices. “European Journal of Dentistry” from Turkey, “Saudi Dental Journal” from Saudi Arabia, and “Iranian Endodontic Journal” and “Journal of Lasers in Medical Sciences” both from Iran had the highest ranks in the SCImago portal and the highest scores in bibliometric indices amongst the MENA dental journals.